Power moves (Long term weight training for sprint, hurdle & jumping events) - Schexnayder, B. (Techniques Magazine, 2023)
Weight training is a critical piece in the athletic development program for practically any sport, and the sprint, hurdle, and jumping events are no different. A well organized, properly administered weight program is a part of every successful program. Generic training is never a good idea, and training simply to produce fatigue should not be an option, Training should be purposeful and organized so that every exercise, set and repetition serves a purpose and fills a logical position.